Examining internal and external job resources in child welfare: Protecting against caseworker burnout. (July 2018) - He, Amy S.; Phillips, Jon D.; Lizano, Erica L.; Rienks, Shauna; Leake, Robin
Abstract: Given intense job demands, it is not surprising that job burnout is a consistent threat to the well-being and retention of the child welfare workforce. Guided by central postulates of the Job Demands and Resources (JD-R) model which suggests that job burnout develops because of experiences of high work demands coupled with low resources in the workplace, we applied a conceptual model of job burnout (client and work related) that accounts for both internal and external resources available to child welfare workers. Findings among child welfare caseworkers from three states ( N  = 1917) indicate that job demands (stress and time pressure) were positively related to client- and work-related burnout. Additionally, both internal and external resources moderated the relationships between job demands and client- and work-related burnout. Study findings have workforce management implications in the child welfare sector, including the role resources might play in mitigating the negative impact of job demands on burnout in the child welfare workforce.